How Well are Job Burnout and Engagement Related to Public Service Motivation Among Civil Servants? Empirical Evidence in Pandemic Setting - Iin Agustina; Bella Rindiani; Aprillia Dellarosa; Alam A Gunawan; Septian Herdiana (Jurnal Ilmu Manajemen Advantage, 2022)
This study aims to analyze how job burnout and engagement could affect public service motivation among civil servants in Bandung, West Java, Indonesia. The sample in this study was employees who worked in public organizations in Bandung Raya, West Java Province, Indonesia. By using a purposive sampling technique, about 73 civils who are willing to become respondents and participate in the research. The results reveal that all hypotheses proposed in the study can be confirmed. An important finding from this study is the mediating role of job engagement on the effect of job burnout on public service motivation. Although job burnout can directly reduce job engagement and public services motivation, if public organizations can manage job engagement better, they will be able to increase public services motivation even more. The development of relationships between concepts and patterns that apply in context and other research designs is highly recommended to uncover interesting things that may not have been found in this study. Recommendations for further research are to expand the scope of the research object, in addition to re-examining the validity of the model, it is also expected to reveal other things that are important information for policymakers and leaders in public sector organizations.